Disentangling Crowdfunding from Fraudfunding - Moein Karami; Douglas Cumming; Lars Hornuf; Denis Schweizer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Using Kickstarter and Indiegogo, the two largest crowdfunding platforms, we conduct an exhaustive search of all fraud cases from 2010 through 2015. We present evidence that fraudsters in crowdfunding markets have specific characteristics: they are less likely to have engaged in prior crowdfunding activities, they are less likely to have a social media presence, and they are more likely to provide poorly worded and confusing campaign pitches.
Keywords: G21; G24; G32; K22; L26; 330